Relationships Between Climate Mitigation Actions and Mental Health: A Systematic Review of the Research Landscape - Robison, Rosie; van Bommel, Maxine; Rohse, Melanie (Frontiers in Climate, 2022)
The impacts of climate change-related events on mental health and emotional wellbeing have gained increased attention in recent years. However, research exploring how climate mitigation actions, i.e. moving towards more sustainable lifestyles, interrelates with mental health is arguably a more hidden body of work. This research is scattered across fields and uses a variety of concepts to explore both the role that emotional and mental health management skills may play in enabling personal climate mitigation actions, as well as the ways in which accelerated transitions towards lower carbon emitting ways of life may impact on mental wellbeing at both an individual and societal level. Our systematic review therefore aims to bring together for the first time research which has been undertaken in the emerging area of mental health and climate mitigation action. To facilitate this exploration, systematic Web of Science searches were undertaken which: (1) identified 165 publications exploring climate change and mental health issues broadly, and (2) identified 26 publications relating climate mitigation actions with specific mental health impacts (anxiety, trauma, suicide, OCD). We find that mental health is primarily being seen as an outcome of climate change impacts, not a factor in our ability to work to avoid them. The limited work which does exist around mental health and climate mitigation action focusses on anxiety and trauma and spans the psychological, psychosocial, public health and wider social sciences. Anxiety and trauma-avoidance has been found to both stimulate and stifle action in different circumstances. One explanation may be the role organisations (and other social structures like family or gender identities) play in maintaining cultures which either support social defences against mitigation action or provide emotionally-safe spaces for building climate commitment. Anticipating potential mental health impacts during policy planning – and putting in place appropriate support measures – will be vital to successfully meeting climate targets. We therefore conclude with implications for policy and practice, including the need to: build appropriate psychological support into behaviour change interventions, work with groups who can provide each other with emotional peer support, and ensure health and social care professionals are given adequate training.